Invertebrate genetic models of amyotrophic lateral sclerosis - Zhou, LiJun; Xu, RenShi (Frontiers in Molecular Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) is a common adult onset neurodegenerative disease featured by the progressive death of motor neurons in cerebral cortex, brain stem and spinal cord. The exact mechanisms involved in the pathogenesis of ALS have remained elusive yet. The current consensuses about the pathogenesis of ALS suggest that the interaction between the genetic susceptibility and the harmful environmental factors may be the promising cause triggering the onset of ALS. The investigation of the putative harmful environmental factors has been the subject of much ongoing researches, but the transgenic animal models to study ALS have obtained some valuable information for the onset of ALS. Here, we will review the current common invertebrate genetic models that have been used to study the pathology, pathophysiology and pathogenesis of ALS. Meanwhile, the considerations of the usages, advantages, disadvantages, cost and availability of each invertebrate model will also be discussed.